A review on Africa energy supply through renewable energy production: Nigeria, Cameroon, Ghana and South Africa as a case study - (:unkn) unknown (My University, 2021)
In this study, the importance of renewable energy as a complement to meeting the energy demand in Africa was investigated. In most African countries, the larger percentage of power generation is from fossil fuel-based energy sources, and without a doubt, this can be complemented with renewable energy to meet the demand per country and the global interest on climate change. Nigeria, Cameroon, Ghana and South Africa are among the leading African countries that are blessed with an abundance of renewable energy resources, which have the potentials to improve their respective energy generation potentials; thereby, contributing to the socio-economic growth, promote industrialization, reduce global warming and create green jobs. Despite the abundant renewable energy sources in these countries, they are yet to fully harness the potentials, therefore, resulting in their deficiencies in contributing to the electrical power generation per country. The bulk of the problems associated with renewable energy in African countries are: little interest and lopsided policy on renewable energy, enforcing existing policies, high renewable energy tariff, and lack of adequate infrastructure. The current study discusses the ways by which conscious decisions and policy of governments, alongside the stakeholders’ dedication can ensure sustainable energy supplies. Based on the findings of the study, renewable energy-based power generation can greatly reduce greenhouse gases. Also, subsidizing the tariff levied on renewable can promote energy generation leading to job creation through energy generation from renewable resources.
Keywords: African Research